The construction of historical-cultural identity in the school space and the teaching of Physical Education (Research, Society and Development, 2020)
This article presents a work with Afro-Brazilian dance associated with the construction processes of the cultural historical identity, highlighting how we can approach this issues in Physical Education teaching, integrating it with the curriculum proposal and other matters, thus developing dance activities that can offer the student the possibility of expression. We adopted Participant Research with the purpose of getting closer to the reality of people in conjunction with the investigation of our own practice as a Physical Education teacher. Throughout the process, based on the analysis of the information recorded in the notebook, we observed as a result of this work the changes in students' conceptions about racism and African culture. We believe that by introducing cultural practices of African origin in the school, we are allowing subjects to have contact with part of their history, as well as enabling feelings of representation and identification. As a result, we highlight the possibility of using Physical Education classes to value Afro-Brazilian culture, with educational practices that address racial issues and collaborate to eliminate racism, prejudice, discrimination and strengthen the construction of cultural historical identity.